Principles of Clinical Cancer Genetics A Handbook from the Massachusetts General Hospital - Chung, Daniel C.; Haber, Daniel A.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
Advances in genetics are transforming estimates of an individual$1 (Bs risk of developing cancer and approaches to prevention and management of cancer in those who may have increased susceptibility. Identifying and caring for patients with hereditary cancer syndromes and their family members present a complex clinical, scientific and social challenge. This textbook, by leading experts at Massachusetts General Hospital Cancer Center, highlights the current understanding of the genetics of hereditary cancers of the breast, ovary, colorectum, stomach, pancreas, kidney, skin, and endocrine organs. Practical guidelines for the use of genetic testing, cancer screening and surveillance, prophylactic surgery, and promising targeted therapeutic agents are discussed. In addition, ongoing research involving genome-wide screens to identify novel modest risk-associated genetic loci are explored, along with new approaches to the application of genetic markers in guiding therapeutic options.s
Basic Principles of Cancer Genetics -- Principles of Cancer Genetic Counseling and Genetic Testing -- Genetics of Hereditary Breast Cancer -- Surgical Management of Hereditary Breast and Ovarian Cancer -- Hereditary Colon Cancer: Colonic Polyposis Syndromes -- Hereditary Colon Cancer: Lynch Syndrome -- Hereditary Pancreatic Cancer -- Hereditary Diffuse Gastric Cancer -- Familial Renal Cell Cancers and Pheochromocytomas -- Familial Atypical Mole Melanoma (FAMM) Syndrome -- Multiple Endocrine Neoplasia -- Pediatric Malignancies: Retinoblastoma and Wilms$1 (BTumor -- Neurofibromatosis and Schwannomatosis -- The HapMap Project and Low-Penetrance Cancer Susceptibility Alleles -- Somatic Genetic Alterations and Implications for Targeted Therapies in Cancer (GIST, CML, Lung Cancer).s
Keywords: Medicine; Human genetics; Oncology; Medicine & Public Health; Oncology; Human Genetics